Property marketing strategy through digital platform of real estate agency in Malaysia - Tan, Jia Ying (2022)
Digital revolution has allowed the digital technologies being used to serve customers real time and the communication has become immediate. Besides to avoid the time consuming in delivering the information through Internet, it also helps to understand the requirement and problem of the customers better. Thus, the property agents ought to adapt and adopt in applying digital technologies to promote their properties to increase the competitive advantage in this digitalization era. Other than that, there are various impacts of adopting digital marketing in property market which discussed by the previous researchers. Thus, it is imperative to assess the impacts of adopting digital marketing in real estate agency practice in Malaysia. The researcher carried out the data collection through the qualitative unstructured interview with seven experienced registered estate agents from the top ten well-known real estate agency firms in Malaysia. After analysing and interpretating the data of interview findings using qualitative content analysis, the study found that more than half of the respondents are adopting social media marketing in promoting their properties on digital platforms. The adoption of digital marketing by registered estate agents in Malaysia depend on the types of property market involved, types of properties promoted, and subject to the types of appointment of the clients. Additionally, this study discovered that the application of digital marketing affected the relationship between agents and customers due to its greater exposure and customer engagement. This study had proposed the strategies to help the registered estate agents to utilise the digital marketing wisely and professionally. This study found that, through the training or courses, it will help to improve the service quality to the public. By performing the trustworthy services, it will help in building the customer’s loyalty to the real estate agency firms. When the brand and image of the estate agency firms being boosted, it will increase the sales generation and firms’ earning.